PENGARUH HARGA, KUALITAS PRODUK, KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN AYAM GORENG NELONGSO NGINDEN SEMOLO SURABAYA - Dita Puspita Sari; Ony Kurniawati (STIE Mahardhika, 2022)
Price is one of the factor influences consumer when making a purchase decision affecting both product quality and service quality. The study uses quantitative data. the population and sample are consumers of Nelongso Fried Chicken Nginden Semolo Surabaya , totaling 90 respondents. The instrument in this study used a Likert scale and the technique used was the non-probability sampling technique with the accidental sampling approach. By using the formula Hair et al. The results showed that the price (X1) the sig value obtained t sig of 0.000 < 0.05, the Product Quality (X2) sig value obtained 0.037 < 0.05, Service Quality (X3) the sig value obtained 0.002 < 0.05. And the F value with a significant level of 0.000 <0.05. Therefore, it can be said that price variables (X1), product quality (X2), and quality of service (X3) have a great influence on the purchase decision (Y) of Nelongso Fried Chicken, Nginden Semolo Surabaya at the same time. While the R Square test was obtained at 0.634 this means that 63.4% of the independent variables, Price (X1), Product Quality (X2) and Quality of Service (X3) dependent variables, Purchase Decision (Y). To do impact and the remaining 36.4% are affected by other factors